THE ACTIVITIES OF THE NATIONAL BANK OF UKRAINE ON THE OPEN MARKET: OPERATION WITH CERTIFICATES OF DEPOSITS - Harkusha , Yu.O. (The actual problems of regional economy development, 2016)
In the article investigated the activities of the National Bank of Ukraine on the open market. The analysis of operations of the National Bank of Ukraine banks to raise funds placing deposit certificates. Defined impact operations of the central bank's own debt securities to trading volumes deposit certificates of the National Bank of Ukraine on the stock market and the credit activity of banks. Identified problems interest rate policy and the ways to overcome them. JEL: E 58